Peripheral Blood Biomarkers Associated With Improved Functional Outcome in Patients With Chronic Left Ventricular Dysfunction: A Biorepository Evaluation of the FOCUS-CCTRN Trial - Chacon Alberty, Lourdes; Perin, Emerson C.; Willerson, James T.; Gahremanpour, Amir; Bolli, Roberto; Yang, Phillip C.; Traverse, Jay H.; Lai, Dejian; Pepine, Carl J.; Taylor, Doris A. (Frontiers in Cardiovascular Medicine, 2021)
Cell therapy trials for heart failure (HF) have shown modest improvement; however, the mechanisms underlying improvement in some patients but not others are not well understood. Although immune cells are important in the course of HF, our understanding of the immune processes in HF is limited. The objective of this study was to evaluate associations between temporal changes in peripheral blood (PB) cell subpopulations and improved outcome in patients with chronic ischemic cardiomyopathy after bone marrow-derived mononuclear cell therapy or placebo in the FOCUS-CCTRN trial. PB was collected at days 0, 1, 30, 90, and 180 from consented participants. We used flow cytometry to compare PB populations in patients with the best (cohort 1) or worst functional outcome (cohort 2) in three primary endpoints: left ventricular (LV) ejection fraction, LV end-systolic volume, and maximal oxygen consumption. A linear mixed model was used to assess changes over time in 32 cell populations. The difference between each time point and baseline was calculated as linear contrast. Compared with cohort 2, patients who improved (cohort 1) had a higher frequency of CD45+CD19+ B cells at days 0, 1, 90, and 180. CD11B+ cells increased over baseline at day 1 in both cohorts and remained higher in cohort 2 until day 30. CD45+CD133+ progenitor cells decreased over baseline at day 30 in cohort 1. We identified specific cell subpopulations associated with improved cardiac function in patients with chronic LV dysfunction. These findings may improve patient selection and prediction of outcomes in cell therapy trials.